ADOPSI XBRL TERHADAP PERILAKU PERDAGANGAN INVESTOR DI BURSA EFEK INDONESIA - Razak, Linda A.; Pontoh, Grace T.; Yamin, Muhammad (Jurusan Akuntansi Fakultas Ekonomi dan Bisnis Universitas Tadulako, 2019)
This study aims to investigate the impact of XBRL adoption to trade behavior of investors in the Indonesia Stock Exchange which is reflected by frequency of stock trade. The sample of this study is 34 banks taken randomly from 81 banks listed in the Indonesia Stock Exchange in 2014 and 2016. The data analysis methods used in this study are one way ANOVA for difference test and multiple regression analysis to test the impact of ROA, size and dividend ratio to XBRL adoption. This study found that the frequency of stock trade and ROA as control variable doesn’t change when XBRL is applied. This result is caused by financial data taken when post-XBRL is financial data in 2016, whereas implementation of XBRL has started since 2015. But, size and dividend change in the period of post-XBRL.